Psychological factors in developing high performance athletes - Elbe, A.-M.; Wikman, J. (Routledge handbook of talent identification and development in sport, 2017)
Top-level athletes are often said to have extraordinary personalities and special psychological characteristics (Gould, Dieffenbach & Moffett, 2002). This is not surprising when considering the many years of training needed to achieve athletic success. This long-term engagement in intense training calls for great efforts in dealing with competitive pressure and demands mental strength with regard to endurance, self-motivation and willpower. But while it is somewhat straightforward to specify the physical and physiological skills needed for top performance in a specific sport, it becomes less clear with regard to the psychological skills that are needed. Therefore, the main questions to be addressed in this chapter are: (1) which psychological skills are needed to reach top performance? And (2) (how) can these skills be developed in young talents?